2012
DOI: 10.1111/j.1365-2141.2012.09149.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the D‐‐ phenotype reveals erythrocyte membrane alterations in the absence of RHCE

Abstract: SummaryRed cells with the D--phenotype do not express the RHCE protein because of mutations in both alleles of the RHCE gene. At present, little is known of the effect this has on the normal function of erythrocytes. In this study a group of five families belonging to a nomadic tribe in Malaysia were identified as carriers of the D--haplotype. Analysis of homozygous individuals' genomic DNA showed two separate novel mutations. In four of the families, RHCE exons 1, 9 and 10 were present, while the 5th family p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…43 Individuals expressing RhD but not RhCE (rare D 22 phenotype) show modest alteration of membranes without overt RBC or clinical phenotypes. 50 Although homologous proteins participate in ammonia/ammonium transport and acid/base balance, RhCE and RhD do not. 51,52 Band 3 and GPA are highly expressed membrane proteins important for structural membrane complexes and ion exchange, and carriage of sialoglycoproteins, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…43 Individuals expressing RhD but not RhCE (rare D 22 phenotype) show modest alteration of membranes without overt RBC or clinical phenotypes. 50 Although homologous proteins participate in ammonia/ammonium transport and acid/base balance, RhCE and RhD do not. 51,52 Band 3 and GPA are highly expressed membrane proteins important for structural membrane complexes and ion exchange, and carriage of sialoglycoproteins, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This complex links to spectrin in the cytoskeleton via ankyrin and contributes to maintaining red blood cell shape and ammonia transport (Van Kim et al, 2006). The function of CD47 in this complex remains unclear, but CD47 expression is reduced in individuals lacking specific components of the complex including the RhCE, band 4.2, and RhAG proteins (Mouro-Chanteloup et al, 2003, Cambot et al, 2013, Flatt et al, 2012). Individual variations in Rh expression also alter CD47 expression (Dahl et al, 2003).…”
Section: Proximal Signalingmentioning
confidence: 99%
“…In the description of the last theory, studies showed that a hybrid gene only produced the D antigen [9,10]. Immunoblotting techniques showed that the expression of D antigen and ICAM4 (LW) was increased whereas CD44 antigen and related blood group antigens were reduced [6]. Herewith, we have reported a case of a woman with rare D-phenotype.…”
Section: Introductionmentioning
confidence: 77%
“…In this phenotype, RHCE proteins are not expressed on RBC membrane. After immune stimulus, individuals with D-phenotype produce an alloantibody known as AntiRh17 (AntiHr0) against CcEe antigens that can lead to the development of a hemolytic transfusion reaction (HTR) or hemolytic disease of newborn (HDN) [6][7][8]. Several genetic bases have been known to be responsible for this phenotype: (1) reduced transcription of CE gene, (2) RHCE deletion, (3) gene hybridization between RHD and RHCE genes because of their highly homologous nature.…”
Section: Introductionmentioning
confidence: 99%